AN INTRIGUING CAUSE OF CHRONIC DIARRHEA – PROTEIN-LOSING ENTEROPATHY AS THE PRESENTING MANIFESTATION OF SYSTEMIC LUPUS ERYTHEMATOSUS - H, Satish; M, Hariharan; Patil, Navin; Rao, Karthik; Ommurugan, Balaji; Nayak B, Satish (Asian Journal of Pharmaceutical and Clinical Research, 2017)
ABSTRACT Systemic lupus erythematosus (SLE) is a systemic autoimmune inflammatory disease. It presents with myriad of clinical manifestations affecting every other organ system in human body. The gastrointestinal system is one of the commonest affected and it involves any part of the GI tract with incidences ranging from 1.3% to 27.5%. Gastrointestinal manifestations as a presenting feature of SLE is unusual. Chronic diarrhea due to protein losing enteropathy as the presenting manifestation of SLE is very rare and a diagnosis of SLE should be kept in mind when other systemic manifestations are absent. Hence, we report a 29-year-old female with chronic diarrhea as the main manifestation of SLE.